Yilmak Laundry Machine Maintenance Analysis with Reliability Centered Maintenance (RCM) and Risk Based Maintenance (RBM) Methods (Case Study: Laundry Department of PT. Eratex Djaja) - Roni Dwi Irawan (Universitas Panca Marga, 2022)
PT. Eratex Djaja is a garment company that produces products in the form of apparel. One of the parts in production is the Washing section. There are several machines in the washing section, including: Tonello Machines, Tolkar, Yilmak, Ramsons, Belly. The problem that was found in the Washing section was that the Yilmak Laundry Machine had a high downtime which reached 9180 minutes. This study aims to analyze the system on these machines using the Reliability Centered Maintenance (RCM) and Risk Based Maintenance (RBM) methods. From the analysis of the RCM method, it is known that the components of the Motor Drive, Pulley + V-belt, and shaft + Bushing are critical components. From the calculation of Total Minimum Downtime (TMD), the optimum replacement interval for the Motor Drive component is 25 days, Pulley + V-belt 32 days, and shaft + Bushing 30 days. From the calculation using the RBM method, the value of risk received by PT. Eratex Djaja if the Yilmak Laundry machine is damaged in the amount of Rp. 412,003,141.